The Effect of Work-Life Balance on Employee Job Satisfaction in the Furniture Sales Industry: An Empirical Study Using Non-Parametric Statistical Methods - Nurhalimatussya'diah, Annisa; Irfansyah, Muhammad (Program Studi Ilmu Administrasi Negara FISIP UNPATTI, 2025)
This study aims to analyze the effect of work-life balance on employee job satisfaction in the furniture sales industry. Data was collected using a Google Form questionnaire filled out by 75 respondents working in the furniture sales industry. The results of data analysis using SPSS showed that the data were not normally distributed, so non-parametric statistical methods were used for further analysis. Validity tests showed a significant positive correlation between work-life balance and employee job satisfaction (r = 0.574; p < 0.05). Reliability tests showed that the research instrument was reliable with Cronbach's Alpha values for work-life balance variable (α = 0.870), job satisfaction (α = 0.822), and employee loyalty (α = 0.788). Multiple regression analysis showed that work-life balance and job satisfaction significantly affect employee loyalty with R² = 0.672, meaning that 67.2% of the variation in employee loyalty is explained by these two variables. Job satisfaction proved to have a significant positive effect on employee loyalty (β = 0.662; p < 0.05). This study concludes that companies need to pay attention to the work-life balance of employees to improve their job satisfaction and loyalty. Policies such as flexible working hours, employee welfare programs, and mental health support can be effective strategies to achieve these goals.